Personality, an affective factor that influences young-adult students : speaking teaching strategies - Sáenz Guerra, Jacqueline Aimé (2020)
The present paper aims to introduce how essential is the teacher’s role when using teaching speaking strategies in front of a classroom. The main concern that teachers have is to help learners to develop in a productive form their language proficiency; students’ particular goal is to achieve an efficient, communicative way to express their desires and thoughts. The teacher may adapt his/her personality in the class according to each students’ needs and learning styles. As well, teachers may consider the students’ strengths and areas of opportunity to reinforce their English knowledge. This study is based on the action research methodology in which various instruments, such as observation, survey, and interview, were applied. It was identified that the atmosphere led to an interaction where the students felt comfortable to participate. Similarly, the students significantly perceived the importance of the teacher’s attitude and personality in front of the classroom.